Theoretical Study of Nuclear Flow and Stopping at Intermediate Energies - Deepshikha (My University, 2019)
The nuclear physics field promises a rich variety of interesting phenomena studied both by experimental observations and theoretical calculations. While switching from low incident energy to higher incident energy plenty of phenomenon have been observed. In the present study we have explored different aspects of two phenomena namely collective flow and nuclear stopping using isospin-dependent Quantum Molecular Dynamics (IQMD) model. Initially, author has tried to ruminate the basic collision dynamics and shed light on influence of centrality of nuclear reactions before and after collisions. The central collisions, peripheral collisions and three dimensional trajectory of nucleons have been discussed in detail. The phase space of nucleons in nuclear reactions have also been discussed. The detailed analysis has been made on nuclear stopping using various observable for the mass symmetric and asymmetric reactions. Our study proves that the ratio of width of transverse to longitudinal rapidity distribution i.e., < varxz > is the most suitable parameter to study nuclear stopping. Also, it has been observed that light mass fragments (LMF’s) emitted from participant region can be used as a barometer to study nuclear stopping. Attempts have been made to recognize the aspect of nucleon-nucleon cross-sections, equation of state and width of Gaussian wave packet on memory loss of nucleons. Finally, correlations among nucleons and memory loss have been explored thoroughly. It has been observed that effect of mass asymmetry can be compensated by changing the impact parameter of nuclear reactions. In a comparative study, various mass asymmetric reactions with total mass fixed have been also analyzed and knock off that mass asymmetry of the reaction has a remarkable influence on the dynamics of the reaction. Thus, while studying various phenomena of the heavy-ion reactions at intermediate energies, the mass asymmetry of the reaction should be properly taken into account. Nuclear flow observable have been investigated systematically for the collision of nearly symmetric nuclei. Both balance and transition energies have shown their dependence on various input parameters of the reaction like the composite mass of the colliding nuclei, incident energy and impact parameter. In addition to this, it has been concluded that power law behavior is perceived for both the balance and transition energies. Transition energy is more expedient to analyzing the behavior of compressed nuclear matter. Further, squeeze out phenomenon is helpful to understand the reaction dynamics. The higher harmonics i.e., < v3 > and < v4 > have smaller contribution than < v1 > and < v2 >. The percentage of nucleons participating in flow decreases with increasing order of the harmonics. Lastly, author summarize the work carried out in this thesis along with the future prospects for the extension of present work.
Keywords: Nuclear flow; Collective flow; Memory loss; Multi fragmentation; Equation of state; Iso spin mixing; Transition energy; Elliptic flow; Nuclear stopping